The Kurdish question in Syria and Turkey in the middle of the XX century – beginning of XXI century. - Kurmet., B. M. (Journal of Oriental Studies, 2016)
This article examines the Kurdish quiestion in Sirya and Iraq amd the role of kurds in social and political life of these countries.